The role of social groups in enhancing the sense of social cohesion among rural youth virtual communities - Bolong, Jusang; Sahharon, Hamizah; Omar, Siti Zobidah (Taylor University, 2024)
Promoting unity among Malaysia’s diverse communities relies heavily on social cohesion, an ongoing challenge that requires continuous nurturing and adaptation. One initiative in Malaysia aimed at using social media to bridge cultural divides is the 1Malaysia Wireless Village Project. This project enhances social cohesion and digital unity by enabling locals to engage in conversations and voice concerns about their communities. Hence, this study explores the dynamics of social cohesion, with a particular focus on the moderating effect of social groups, specifically in-groups and out-groups, on Facebook functionality usage among rural youths. The in-group comprises individuals with shared cultural backgrounds residing in the same demographic, while the out-group encompasses those with whom the person has no affiliation or identification. A quantitative approach was employed in this study, involving 300 rural youths aged 15 to 40 from six 1Malaysia Wireless Villages. The study investigates how in-group and out-group dynamics affect the use of Facebook functionality and its impact on social cohesion. The results reveal a strong relationship between the use of sharing and reputation features in Facebook social groups and the perception of social cohesion among rural youths. Notably, the study highlights that young people must actively engage in sharing and building favourable reputations within their groups to enhance social cohesion. Conversely, there was no discernible effect of out-group interactions on social cohesion. The research culminates in the creation of a model intended to improve rural youths’ feeling of social cohesiveness. The approach offers useful information for community development programmes by highlighting the significance of constructive relationships within in-group social circles. The findings also highlight the critical role that social media sites like Facebook play in promoting social cohesiveness and offer a sophisticated understanding of the moderating influence of social group dynamics on the formation of collective unity among heterogeneous populations.